Genetic structure of populations of the Macrobrachium amazonicum complex (Crustacea: Decapoda) based on multiple regions of mitochondrial DNA - Gabriel Monteiro de Lima; Leonardo Milani Fabri; Ítalo Lutz; Luciano Domingues Queiroz; Carlos Murilo Tenório Maciel; Daniela Pereira Garçon; Francisco Assis Leone; Cristiana Ramalho Maciel (Hydrobiologia, 2026)
Macrobrachium amazonicum is a widely distributed freshwater prawn inhabiting river basins across South America. It includes both diadromous and hololimnetic populations, exhibiting notable differences in bioecological, physiological, and reproductive traits. Individuals from the Pantanal region display distinct characteristics that led to their classification as a separate species, Macrobrachium pantanalense . Despite these differences, studies using mitochondrial markers (COI and 16S rRNA) have revealed low genetic divergence, identifying three distinct genetic lineages. This study analyzes multiple mitochondrial genomes from M. amazonicum and M. pantanalense populations, based on transcriptome-derived data, to improve understanding of evolutionary relationships and genetic structure within the “ Macrobrachium amazonicum complex”. Mitogenome coverage ranged from 51.6 to 63.1% in M. amazonicum and 76.8 to 77.0% in M. pantanalense . Interspecific distances between M. amazonicum and M. pantanalense were lower than those typically observed among other Macrobrachium species. Nonetheless, populations of each species showed strong genetic structuring, consistently forming distinct clusters across all phylogenetic reconstructions, both individual and concatenated. The relatively low genetic variation observed could be linked to a recent speciation event, supported by distinct bioecological and physiological traits and patterns of geographic and reproductive isolation within the M. amazonicum complex.